MORPHOLOGICAL AND PALYNOLOGICAL INVESTIGATIONS ON SOME TAXA OF MEDICAGO L. (FABACEAE) GENUS DISTRIBUTING IN ANLIURFA - ALTIN, Fatma; EEN, Cahit; AKAN, Hasan; ETER, Talip (Zenodo, 2021)
In this study, the morphological and palynological features of Medicago noeana Boiss. Medicago coronata (L) Bart., Medicago minima (L) Bart., species belonging to Medicago genus of Fabaceae family distributed in anlurfa province were studied. Within the framework of morphological studies, the field was explored and herbarium samples were examined. Morphological measurements were compared with 'Flora of Turkey'. In the framework of the palynological study, pollen shapes, ornamentations, porus and colpus lengths and widths were examined.
Keywords: Medicago, Morphological, Palynological, anlurfa; 15. Life on land